Timing of Revascularization and Parenteral Antibiotic Treatment Associated with Therapeutic Failures in Ischemic Diabetic Foot Infections - Dominique Altmann; Felix W. A. Waibel; Gabor Forgo; Alexandru Grigorean; Benjamin A. Lipsky; Ilker Uçkay; Madlaina Schöni (MDPI AG, 2023)
For ischemic diabetic foot infections (DFIs), revascularization ideally occurs before surgery, while a parenteral antibiotic treatment could be more efficacious than oral agents. In our tertiary center, we investigated the effects of the sequence between revascularization and surgery (emphasizing the perioperative period of 2 weeks before and after surgery), and the influence of administering parenteral antibiotic therapy on the outcomes of DFIs. Among 838 ischemic DFIs with moderate-to-severe symptomatic peripheral arterial disease, we revascularized 608 (72%; 562 angioplasties, 62 vascular surgeries) and surgically debrided all. The median length of postsurgical antibiotic therapy was 21 days (given parenterally for the initial 7 days). The median time delay between revascularization and debridement surgery was 7 days. During the long-term follow-up, treatment failed and required reoperation in 182 DFI episodes (30%). By multivariate Cox regression analyses, neither a delay between surgery and angioplasty (hazard ratio 1.0, 95% confidence interval 1.0-1.0), nor the postsurgical sequence of angioplasty (HR 0.9, 95% CI 0.5-1.8), nor long-duration parenteral antibiotic therapy (HR 1.0, 95% CI 0.9-1.1) prevented failures. Our results might indicate the feasibility of a more practical approach to ischemic DFIs in terms of timing of vascularization and more oral antibiotic use.